Incarcerated Obturator Hernia in a Scoliotic Patient: A Case Report and Review of Literature - Bedel, Estelle; Baali, Smail; Razanajatovo, Andria; Asensio, Thierry; Zeguem, Salem; Terro, Jad (International Journal of Clinical Research, 2025)
Background: Obturator hernia is a rare entity mainly occurring in cachectic females, which usually end in intestinal obstruction leading to drastic situations due to diagnostic challenges. Case Report: A case of a low Body mass index scoliotic female patient presented with signs of intestinal occlusion, with no other pertinent findings on physical exam. Computed tomography scan has demonstrated an incarcerated right obturator hernia with no intestinal suffering. Laparoscopic exploration has confirmed the diagnosis, but due to uneasy reduction of the incarcerated small bowel loop, an open reduction and hernioplasty was performed, leading to an uneventful postoperative hospital stay and home discharge. Discussion: Anatomically, the obturator foramen is a large aperture formed by the ischium and the pubis. It is oval in males, while triangular and wider in females, leading to a 9 times higher incidence in females. More than 90% of cases present with mechanical intestinal obstruction, manifesting as nausea, vomiting, and a crampy intermittent acute abdominal pain. The sac content is mostly small bowel, but cases of ovaries, Meckel’s diverticulum, appendix, fallopian tube, omentum, and colon have been observed and stated in literature. Conclusion: Obturator hernia is associated with higher mortality rates than other abdominal hernias, hence prompt diagnosis is required, where computed tomography scan is the gold standard. Laparoscopic technique have many advantages, while it is not suitable in septic or unstable conditions. Hernioplasty is superior to herniorrhaphy in clean surgeries.